PEMANFAATAN LIMBAH PADAT PABRIK TAHU SEBAGAI PAKAN KONSENTRAT TERNAK DENGAN PROSES FERMENTASI - Joni Hermana (Purifikasi, 2004)
This research was aimed to determine fermentation influence to soya nutrition. The variations in this research were fermentation period (1 day, 2 days, 3 days, 4 days, 5 days and 6 days) and bio-N concentration (10 ml/2 kg soya waste, 20 ml/2kg tofu waste and 30 ml/2 kg tofu waste). The nutrition which examined with proksimat analysis were rough protein, rough fibre, extract non nitrogen (BETN), rough fat. The result showed that the optimum period of fermentation was 4 days and the effective bio-N concentration was 20 ml/2 kg tofu waste. The rough protein increased to 26,07%, and rough fat increased to 17,35%.